I'm going to be a police officer - Kunhardt, Edith (New York : Scholastic Inc., 1995)
A young girl describes some of the things that her father and other police officers do each day on the job.
"Cartwheel books."
Originally published: I want to be a police officer. New York : Grosset & Dunlap, 1989.
Keywords: Police; Police -- United States; Police; Occupations